Performance: Photographs of a Decade 1959-69 : Backworks? Catalog No B. (New York : Backworks, 1977)
Performers: Kaprow, Allan ; Oldenburg, Claes ; Dine, Jim ; Klein, Yves ; Ono, Yoko ; Higgins, Dick ; Paik, Nam June ; Knowles, Alison ; Vautier, Ben ; etc. Photographers: Baker, Max ; Holmes, Martha ; Hyde, Scott ; Maciunas, George ; Mcelroy, Robert ; Moore, Peter ; Shunk-Kender ; Shustak, Lawrence
Engels
boek